Factors Influencing the Yemeni Customers’ Intention to Adopt Takaful Products - Echchabi, Abdelghani; Ayedh, Abdullah Mohammed (Gadjah Mada International Journal of Business, 2015)
The purpose of this study is to examine the Yemeni customers’ intention to adopt takaful products, and to explore the potential factors that influence their decision. This study applies SEM and one sample t-test to analyse the collected data. The results indicate that among the factors included in this study, only compatibility positively and significantly affects the adoption intention. This is the first study that addresses the adoption of Takaful products in Yemen and the factors that influence it. Furthermore, this study extends the Innovations Diffusion Theory (IDT) by applying it to a different setting.